Calculation of Stress Intensity Factors KI, KII and KIII of Cracked Components Submitted to Flexural and Torsional Loads. (2016) - Isidoro, J.; Martins, Rui F.
Abstract: Components subjected to flexural and torsional loadings, such as power transmission shafts, are elements that sometimes fail due to fatigue crack propagation. Other example of mechanical element that occasionally fail and that can be simultaneously submitted to bending and torsion are endodontic files, which are being widespread used in mechanized endodontic treatments. With the intent of analyzing the influence of bending and torsion on the Stress Intensity Factors (SIF), KI, II, III, at different crack geometries (a/r), two CAD 3D models were created, namely one cylindrical shaft and one endodontic file. The evaluation of KI, KII and KIII for the two components under study was carried out at several points along the crack front using the Finite Element Method (FEM) together with Linear Elastic Fracture Mechanics (LEFM) concepts. The Finite Element Analyses (FEA) carried out shown that flexural loads have a preponderant impact on KI values, although torsion may have influence on it depending on the order of magnitude of the torsional loading values applied on the component. However, when pure torsion loading was considered, KII and KIII values become dominant at crack tip. Finally, numerical results obtained revealed that geometric complexity and reduced dimensions of components can play an important role when analyzing SIF, being this particularly relevant on the case of endodontic file.